THE ROLE OF ZAKAT MANAGEMENT ORGANIZATIONS IN HANDLING THE GALODO DISASTER IN TANAH DATAR REGENCY - Widi Nopiardo; Asrida (Academic Bright Collaboration, 2026)
Focusing on Tanah Datar Regency, this study examines the efforts of Zakat Management Organizations (OPZ) in responding to the Galodo disaster and explores the specific approaches taken by BAZNAS and LAZ. This research employed a descriptive qualitative method with a field approach. To gather information, data were collected through interviews, observation, and documentation. Specifically, in-depth interviews with the OPZ, village government, and affected communities were conducted using a snowball sampling technique. Subsequently, data analysis followed the Miles and Huberman model. The research findings show that the role of OPZ is highly significant in disaster management in Tanah Datar Regency. These roles includes life-saving efforts, the fulfillment of basic needs such as food assistance and temporary shelter, the provision of psychological support, the development of essential infrastructure, and long-term recovery for survivors who fall into the poor category. OPZ has been proven to play a strategic and comprehensive role in disaster management systems. However, this study has limitations, including an observation period only up to early 2025, insufficiently detailed distribution data, and a geographically limited scope confined to Tanah Datar Regency, which restricts the analysis of the long-term economic impacts of this role. This study provides novelty by exploring the role of OPZ in disaster areas, specifically the Galodo disaster in Tanah Datar Regency, West Sumatra.